Potensi Lokal Lembaga Dalam Mewujudkan Kampung Literasi Pesisir Payangan Kabupaten Jember - Kurniawan, Teguh; Indrianti, Deditiani Tri; Fajarwati, Linda (Program Studi Pendidikan Luar Sekolah FKIP Universitas Jember, 2023)
Rural literacy is a container for improving society's human resources by studious interest in reading and knowledge. Where that increase can be felt in terms of education, technology and economics. Therefore, the existence of a local agency has been very helpful in boosting coastal knowledge to advance and expand. The goal of this study is to identify and describe the potential of local agencies on the payable coast known as the dolphin kub (group of joint venture groups). The research site is located on Joint business group “Lumba-Lumba” selected using a stringent area technique. The identification technique of the informer used is an integral sampling. Data collection techniques using observation, interview, and documentation techniques. The authentication technique of data involves extension of participation, persistence in observation, and triangulation. As for the triangulation used were technical triangulation, source triangulation, and time triangulation. Data analysis USES the miles and huberman theory by data collecting, data reduction, data presentation, and data verification. The result of this research is that local institutions' role is crucial to improving community knowledge to advance and expand. Increased public knowledge can be supported by rural communities through the potential of those around and also various forms of activities